A Randomized, Double‐Blind, Placebo‐ and Positive‐Controlled, Three‐Way Crossover Study in Healthy Participants to Investigate the Effect of Savolitinib on the QTc Interval. Issue 5 (5th January 2021) - Sahota, Tarjinder; Dota, Corina D.; Vik, Torbjörn; Yan, Weili; Verheijen, Remy B.; Walker, Stephen; Li, Yan; Goldwater, Ronald; Ghiorghiu, Dana; Mellemgaard, Anders; Ahmed, Ghada F.
Abstract: Savolitinib (AZD6094, HMPL‐504, volitinib) is an oral, bioavailable, selective MET‐tyrosine kinase inhibitor. This randomized, double‐blind, 3‐way, crossover phase 1 study of savolitinib versus moxifloxacin (positive control) and placebo‐evaluated effects on the QT interval after a single savolitinib dose. Healthy non‐Japanese men were randomized to 1 of 6 treatment sequences, receiving single doses of savolitinib 600 mg, moxifloxacin 400 mg, and placebo. The primary end point was time‐matched, placebo‐adjusted change from baseline in the QT interval corrected for the time between corresponding points on 2 consecutive R waves on electrocardiogram (RR) by the Fridericia formula (ΔΔQTcF). Secondary end points included 12‐lead electrocardiogram (ECG) variables, pharmacokinetics, and safety. All 3 treatment periods were completed by 44 of 45 participants (98%). Baseline demographics were balanced across treatment groups. After a single savolitinib 600‐mg dose, the highest least‐squares mean ΔΔQTcF of 12 milliseconds was observed 5 hours postdose. Upper limits of the 2‐sided 90% confidence interval for ΔΔQTcF exceeded 10 milliseconds (the prespecified International Council for Harmonisation limit) 3‐6 hours postsavolitinib but otherwise remained less than the threshold. Savolitinib showed no additional effect on PR, QRS, QT, or RR intervals. A positive ΔΔQTcF signal from the moxifloxacin group confirmed study validity. Savolitinib was well tolerated, with a low incidence of adverse events. In this thorough QT/QTc study, QTcF prolongation was observed with a single savolitinib 600‐mg dose. ECG monitoring will be implemented in ongoing and future studies of savolitinib to assess the clinical relevance of the observed QT changes from this study.